Local measurement of terahertz field-induced second harmonic generation in plasma filaments - Kareem J. Garriga Francis; Xi-Cheng Zhang (Frontiers of Optoelectronics, 2023)
Abstract The concept of Terahertz Field-Induced Second Harmonic (TFISH) Generation is revisited to introduce a single-shot detection scheme based on third order nonlinearities. Focused specifically on the further development of THz plasma-based sources, we begin our research by reimagining the TFISH system to serve as a direct plasma diagnostic. In this work, an optical probe beam is used to mix directly with the strong ponderomotive current associated with laser-induced ionization. A four-wave mixing (FWM) process then generates a strong second-harmonic optical wave because of the mixing of the probe beam with the nonlinear current components oscillating at THz frequencies. The observed conversion efficiency is high enough that for the first time, the TFISH signal appears visible to the human eye. We perform spectral, spatial, and temporal analysis on the detected second-harmonic frequency and show its direct relationship to the nonlinear current. Further, a method to detect incoherent and coherent THz inside plasma filaments is devised using spatio-temporal couplings. The single-shot detection configurations are theoretically described using a combination of expanded FWM models with Kostenbauder and Gaussian Q-matrices. We show that the retrieved temporal traces for THz radiation from single- and two-color laser-induced air-plasma sources match theoretical descriptions very well. High temporal resolution is shown with a detection bandwidth limited only by the spatial extent of the probe laser beam. Large detection bandwidth and temporal characterization is shown for THz radiation confined to under-dense plasma filaments induced by < 100 fs lasers below the relativistic intensity limit. Graphical Abstract